ASAL-USUL, BENTUK, DAN EKSISTENSI TARI LANGSIR DARI ETNIK HALOBAN - Dharma Kelana Putra (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2022)
Langsir dance is one of the traditional dances of Haloban ethnic, which lives in Tuangku Island, Aceh Singkil Regency. This dance was lost for 20 years, yet it is brought back without any government intervention. This phenomenon leads to the assumption that the traditional dance is not only played for entertaining people, but it also contains more values. This research was conducted using a descriptive qualitative method, which aims to describe langsir dance as it is. Primary data were collected by using observation techniques and in-depth interviews. Meanwhile, secondary data were obtained from literature and documentation of photos and video recordings. Langsir dance turns out to have unique elements that are different from other local dances, such as aesthetic floor patterns, thirtytwo movement variations instructed by the instructor, as well as a combination patterns of coherent and chronological movement. Although this dance was not played for more than 20 years, the knowledge of this dance is still alive in the collective memory of the community. Therefore, when the young generation of Haloban are inspired to learn about their culture, this art is able to be revived even without any government’s revitalization program.